Medication use in Italian nursing homes: preliminary results from the national monitoring system - Zito, S.; Poluzzi, E.; Pierantozzi, A.; Onder, G.; Da Cas, R.; Ippoliti, I.; Lunghi, C.; Cangini, A.; Trotta, F. (Frontiers in Pharmacology, 2023)
Background: The aging population has increased concerns about the affordability, quality, and nature of long-term care for older people, emphasizing the role of nursing homes. Unlike acute hospital and primary care, there is a lack of drug consumption data in long-term care to understand regional or national healthcare policies. Objectives: This study aimed to describe medication consumption by older adults and expenditure in Italian nursing homes (NH). Methods: Data on drug consumption and costs from the administrative medicine informational flows that detect medicines packages supplied to patients in health facilities and NHs were used. Data on the characteristics of the healthcare residence were from the Italian Health Ministry. Records for the year 2019, selecting the nursing homes exclusively providing elderly or mixed (elderly and disable) were used. Results: In 2019, the total expenditure on medicines in NHs amounted to 25.38 million euros, the average cost to 1.30 and the expenditure per bed to 436.18 euros. Cardiovascular drugs were the highest-consuming therapeutic class (177.0 defined daily doses – DDD/100 days of NH stay; 22.2 % of total) followed by drugs acting on the alimentary tract (167.6 and 21.0%) and metabolism (160.4 and 20.1%). The treatment of hypertension and heart failure was widely the most frequently used, with the consumption being driven mainly by furosemide and ramipril. Antiulcer drugs were used on average in more than half of the days of NH stay (58.5 DDD/100 days of NH stay), representing a therapeutic category for which deprescribing initiatives are recommended. On average, almost all patients received a dose of benzodiazepines, antipsychotics and antidepressants (37.6, 35.9, and 17.7 DDD/100 days of NH stay, respectively), confirming the high prevalence of use for these medicines. Antibiotics reached 6.8 DDD/100 days of NH stay. Conclusions: The availability of data in this specific setting allows the identification of the main interventions toward improving appropriateness and represents a challenge for drug utilization research. Data from this study suggest that proton pump inhibitors (PPI), benzodiazepines and antibacterials can be areas of improving prescribing appropriateness.